A troubleshooting guide for writers : - Clouse, Barbara Fine (Mc Graw Hill, 2005)
This brief rhetoric and reference for academic and business writers provides over 280 writing strategies for solving problems at every stage of the writing process--from idea generation through editing. The book's practical approach not only helps writers with broader challenges,such as planning and organization, but also with specific style and grammar issues that can derail the writing process.